Connecting the building blocks of Open Science: an ecological approach - Mounier, Pierre (Septentrio Conference Series, 2022)
Open Science covers a large panel of activities aimed at making research more transparent and collaborative. Several definitions provide lists of different components of open science, which creates the need to imagine how to connect these components together. However, the necessary work to interconnect open science services and tools must be completed by a holistic approach that considers open science as an ecosystem producing a “milieu” of knowledge and supported by a vibrant community gathered around shared values. It leads to an ecological approach of open science where the web of interactions within the ecosystem defines its elements rather than the opposite.